2023
DOI: 10.1038/s41467-023-37083-x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity maturation generates pathogenic antibodies with dual reactivity to DNase1L3 and dsDNA in systemic lupus erythematosus

Abstract: Anti-dsDNA antibodies are pathogenically heterogeneous, implying distinct origins and antigenic properties. Unexpectedly, during the clinical and molecular characterization of autoantibodies to the endonuclease DNase1L3 in patients with systemic lupus erythematosus (SLE), we identified a subset of neutralizing anti-DNase1L3 antibodies previously catalogued as anti-dsDNA. Based on their variable heavy-chain (VH) gene usage, these antibodies can be divided in two groups. One group is encoded by the inherently au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…It has also been reported that a group of human monoclonal antibodies cross-reactive with dsDNA, Crithidia luciliae, histone, and apoptotic Jurkat cells protected NETs from digestion via micrococcal nuclease or DNase I. Interestingly, another group of antibodies which were specific to dsDNA did not show significant protection [65]. In a different context, monoclonal antibodies to DNase1L3 protected chromatin from degradation with this enzyme [10]. DNase1L3 is a member of the DNase1 family, which is responsible for the DNase activity in plasma together with DNase1 itself.…”
Section: Aggravation Of Ifn Signaturementioning
confidence: 98%
See 1 more Smart Citation
“…It has also been reported that a group of human monoclonal antibodies cross-reactive with dsDNA, Crithidia luciliae, histone, and apoptotic Jurkat cells protected NETs from digestion via micrococcal nuclease or DNase I. Interestingly, another group of antibodies which were specific to dsDNA did not show significant protection [65]. In a different context, monoclonal antibodies to DNase1L3 protected chromatin from degradation with this enzyme [10]. DNase1L3 is a member of the DNase1 family, which is responsible for the DNase activity in plasma together with DNase1 itself.…”
Section: Aggravation Of Ifn Signaturementioning
confidence: 98%
“…However, recent advances in molecular technology have facilitated the production of human monoclonal anti-DNA antibody-like proteins via the transfection of HEK 293T cells with immunoglobulin heavy chain genes identified from a single B cell from the peripheral blood of a patient with SLE [9]. Applying this technique to analyze the variable region gene's use of anti-DNase1L3 neutralizing antibodies, interestingly, some were found to have been derived from anti-DNase1L3 germline-encoded precursors which acquired cross-reactivity to dsDNA following somatic hypermutation [10]. Another study reported that some mouse anti-dsDNA monoclonal antibodies were cross-reactive with spermatid nuclear transition protein 1 [11].…”
Section: Generation Of Anti-dna Antibodiesmentioning
confidence: 99%
“…While anti-lipoglycan antibodies naturally arise in the absence of previous immunization, which therefore may be considered a form of natural antibodies, [ 63 ] the pathogenic potential of some clones of anti-DNA antibodies has been well established. [ 65 ] Future studies will be needed to determine if the novel lipoglycan produced by some R. gnavus strains can be utilized as a biomarker for lupus nlupus (LN) disease.…”
Section: Studies Of the Gut Microbiome In Cohorts Of Sle Patientsmentioning
confidence: 99%
“…Anti-dsDNA Abs correlate with disease flares, hypocomplementemia, and lupus nephritis and encompass a heterogenous pool of autoantibodies with distinct physicochemical properties. Autoantibodies which crossreact with ds-DNA and other self-antigens and are among the most pathogenic, and include those that also recognize a-actinin to mediate lupus nephritis (5,6), those that cross react with the N-methyl-D-aspartic acid receptor to increase risk of lupus neuropsychosis (7), and those that neutralize DNASE1L3 and are found in patients presenting with higher disease activity scores (8).…”
Section: Introductionmentioning
confidence: 99%
“…Soon thereafter, a second population of patients with a pathogenic variant of DNASE1L3 that reduced plasma enzyme concentration by about 80% -R206C (rs35677470) -was found in thousands of patients with lupus, rheumatoid arthritis, and scleroderma, an association that places individuals with this variant at risk for autoimmune disease (13)(14)(15)(16)(17)(18)(19). Finally, patients with neutralizing autoantibodies to DNASE1L3 that also bind with high affinity to dsDNA were recently identified in about 30% of patients with SLE (20), and these patients were found to present with more aggressive disease characterized by higher SELENA-SLEDAI scores at presentation and activated interferon stimulated gene and neutrophilic activated gene cluster signatures (8).…”
Section: Introductionmentioning
confidence: 99%